The research progress in the interaction between Candida albicans and cancers - Yu, Dalang; Liu, Zhiping (Frontiers in Microbiology, 2022)
Candida albicans is an opportunistic pathogenic fungus, which tends to infect the host with defective immune function including cancer patients. A growing number of studies have shown that C. albicans infection increases the host susceptibility to cancer such as oral, gastric, and colorectal cancer. Cancer and anti-cancer treatment may also affect the colonization of C. albicans. C. albicans may promote the development of cancer by damaging mucosal epithelium, inducing the production of carcinogens, triggering chronic inflammation including Th17 cell-mediated immune response. In this article, we aim to elaborate the interaction between C. albicans and cancers development and summarize the potential molecular mechanisms, so as to provide theoretical basis for prevention, diagnosis and treatment of cancers.